Feasibility of Right Upper Transversal Hepatectomy in the Absence of an Inferior Right Hepatic Vein: New Insights regarding This Complex Procedure. (8th March 2021) - Makdissi, Fabio Ferrari; Kruger, Jaime Arthur Pirola; Jeismann, Vagner Birk; Herman, Paulo
Abstract : Background . Right upper transversal hepatectomy (RUTH) is defined as the removal of liver segments 7, 8, and 4A with ligature of the right and middle hepatic veins and is considered one of the most complex techniques of parenchymal-sparing hepatectomies. This procedure can be performed, without venous reconstruction, if collateral veins are present communicating within remnant liver segments to a large inferior right hepatic vein and/or to the left hepatic vein. This venous network could maintain outflow from the inferior right segments (S5, S6) to the left liver when a RUTH is performed, even in the absence of an inferior right hepatic vein. The aim of this study is to present our experience with RUTH without venous reconstruction in patients with and without the presence of an inferior right hepatic vein (IRHV). Methods . Patients submitted to RUTH for treatment of liver metastases were selected from our database. The presence of an IRHV, clinical and surgical characteristics of the patients, immediate outcomes, viability of liver segments 5 and 6, and long-term survival were analyzed. Results . RUTH was successfully performed in four patients. In two patients, IRHV was not present, but intrahepatic communicating veins between proximal right and middle hepatic veins and left hepatic vein were present. No venous reconstructions were performed. Mild congestion of the inferior right segments occurred in the patients where there was no IRHV but no immediate, early, or late complications were observed. Conclusions . RUTH is feasible and can be performed even in the absence of an IRHV, without venous reconstruction. Some degree of congestion of the right inferior liver segments might occur when an IRHV is absent, yet this is not clinically significant when communicating veins are present. Maximum parenchyma preservation might prevent postoperative liver failure and allow repeated resections in case of hepatic recurrence.